Effective expression of recombinant Staphylococcus aureus clumping factor and it immunobiological activity - Ivanova, Victoria (My University, 2001)
Fragments of the clfA gene coding for clumping factor of S.aureus were cloned into the expression plasmid pQE30 in E.coli XLI-Blue cells. It has been shown the reducing of the strain efficiency and the elimination of the plasmid during the cultivation of a producer. Several methods for raising the amount of plasmid-containing cells and increasing the yield of recombinant protein were proposed.
Keywords: clumping factor; пластівцевоутврюючий фактор; хлопьеобразующий фактор; Staphylococcus aureus; IPTG; stability of the plasmid; cultivation; expression; золотистий стафілокок; стабільність плазміди; культивування; експресія; золотистый стафилококк; стабильность плазмиды; культивирования; экспрессия; кафедра експертизи харчових продуктів